Individual variation in simulated fetal SAR assessed in multiple body models - Abaci Turk, Esra (Magn Reson Med, 2019)
PURPOSE: We generate 12 models from 4 pregnant individuals to evaluate individual differences in local SAR for differing body habitus and fetal and maternal positions. METHODS: Structural MR images from four pregnant subjects (including supine and left-lateral maternal positions) were manually segmented to create 12 body models by rotating the fetus, modifying the fat content and altering the maternal arm position in one of the subjects. Electromagnetic simulations modeled at 3T determined the average and peak local SAR in the maternal trunk, fetus, fetal brain, and amniotic fluid. RESULTS: We observed a significant range of fetal and maternal peak local SAR across the models (maternal trunk: 19.14 to 44.03 W/kg, fetus: 9.93 to 18.79 W/kg, fetal brain 3.36 to 10.3 W/kg). We found that maternal body habitus changes introduced a significant variation in the maternal peak local SAR, but not the fetal local SAR. However, the maternal position (either rotating the mother to left-lateral position or altering the arm position) introduced changes in fetal peak local SAR (range: 11.9 to 17.9 W/kg). Rotating the fetus also introduced variation in the fetal and fetal brain peak local SAR. CONCLUSION: The observed variation in SAR emphasizes the need for more anatomical models to enable better safety management of individuals during fetal MRI, including a wider range of gestational ages.